2018
DOI: 10.1159/000491776
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-29a-3p Downregulation Causes Gab1 Upregulation to Promote Glioma Cell Proliferation

Abstract: Background/Aims: Glioma causes significant human mortalities annually. Molecularlytargeted therapy is a focus of glioma research. Methods: Grb2-associated binding 1 (Gab1) expression and microRNA-29a-3p ("miR-29a-3p") expression in human glioma cells and tissues were tested by Western blotting assay and qRT-PCR assay. shRNA/siRNA strategy was applied to silence Gab1 in human glioma cells. miR-29a or anti-sense miR-29a construct was transfected to human glioma cells. Cell proliferation was tested by BrdU ELISA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 48 publications
(55 reference statements)
0
25
0
Order By: Relevance
“…miR-29b leads to retarded growth of intestinal epithelial cells and suppressing GAB1 expression induces apoptosis (An et al 2016). In addition, decreased miR-29a-3p expression gives rise to enhanced proliferation of glioma cells via the upregulation of GAB1 (Shao et al 2018). The critical pro-survival role of GAB1 was also indicated in rat neonatal cardiomyocytes as overexpressed GAB1 was found to result in reduction of apoptosis (Cherif et al 2015).…”
Section: Discussionmentioning
confidence: 96%
“…miR-29b leads to retarded growth of intestinal epithelial cells and suppressing GAB1 expression induces apoptosis (An et al 2016). In addition, decreased miR-29a-3p expression gives rise to enhanced proliferation of glioma cells via the upregulation of GAB1 (Shao et al 2018). The critical pro-survival role of GAB1 was also indicated in rat neonatal cardiomyocytes as overexpressed GAB1 was found to result in reduction of apoptosis (Cherif et al 2015).…”
Section: Discussionmentioning
confidence: 96%
“…The transcription of ERBB3 was regulated by several transcriptional factors, including SOX10 and FoxO3a . It was reported that transcription of GAB1 could be regulated by RARα and several microRNA, such as miR‐150 and miR‐29a‐3p . As for PIK3R3, its transcription was reported to be regulated by SREBP1c and TGF‐β signaling .…”
Section: Discussionmentioning
confidence: 99%
“…About miR-101-3p, it has been reported to a diagnostic biomarker for identifying heart transplant patients with acute cellular rejection (36). Furthermore, it has been demonstrated that the target of miR-29a-3p is Gab1 (37), which plays an vital role in inflammation by inhibiting activation of NK-κB. The remarkable capability of NK-κB is to trigger inflammation by inducing genes expression, including IL-1β, IL-6 and TNF-α (38, 39).…”
Section: Discussionmentioning
confidence: 99%